Uji Coba Fitoremediasi Tanaman Kangkung Air pada Limbah Cair Tahu - Indrawati, Dessy; Ndibale, Wa; Wibowo, Dwiprayogo (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2025)
Tofu industry wastewater contains high levels of organic pollutants, and its direct discharge into water bodies can cause significant environmental damage. Phytoremediation using water spinach (Ipomoea aquatica) offers a simple, low-cost, and eco-friendly method for treating such wastewater. This study aims to analyze changes in BOD, COD, TDS, and TSS levels in tofu wastewater before and after phytoremediation using water spinach. The research involved the preparation of growth media and the collection of tofu wastewater samples, followed by an 11-day phytoremediation process. The treatments varied based on plant biomass (200 grams and 400 grams) and plant age (25 days and 40 days). The most effective treatment was achieved using 400 grams of 40-day-old water spinach, which reduced TSS levels by 23.07% and TDS levels by 12.1%. However, the phytoremediation process in this study was not effective in reducing BOD and COD concentrations.